Evaluation of the relationship between left atrial strain and exercise tolerance in patients with hypertrophic cardiomyopathy by treadmill stress echocardiography - Su, Ye; Li, Chunmei; Yin, Lixue (Frontiers in Cardiovascular Medicine, 2023)
Objective The aim of this study was to evaluate the left atrial strain (LAS) in patients with HCM by treadmill exercise stress echocardiography combined with three-dimensional speckle tracking technology (3DSTI) for predicting exercise tolerance. Methods A total of 97 HCM patients who underwent treadmill exercise stress echocardiography were recruited in Sichuan Provincial People's Hospital from January 2018 to January 2021, and 30 control subjects were selected as the normal group. HCM patients with metabolic equivalents (METS) ≤ 6.0 were included in the HCM-1 group, while those with METS > 6.0 were included in the HCM-2 group. LAS and exercise tolerance were analyzed; the ultrasound parameters that could predict a decrease in exercise tolerance were screened; and a predictive model was constructed. Results METS, Rest-LASr, Rest-LAScd and Rest-LASct were significantly lower in HCM patients than those in normal controls. There was a significant difference in age, Target_HR, LVMI, LAVI, E/e'-Rest, E/e'-Peak, Rest-LASr, Rest-LAScd, and Rest-LASct between the HCM-1 and HCM-2 groups. LASr is an independent resting echocardiographic predictor of METS≤6.0. LASr remained significant for predicting different subtypes (AHCM, asymmetric HCM, and obstructive HCM). Rest-LASr (AUC 0.990) is better in predicting METS≤6.0 than Peak-E/e' (AUC 0.753). A multivariate model (LASr+Age+Target_HR) was established for METS prediction. Conclusion LASr has the strongest association with METS≤6.0. LASr is an independent resting predictor of METS≤6.0, which has a good performance in different subtypes of HCM. Compared with the traditional parameters Peak-E/e' and Rest-E/e', Rest-LASr is best predictor. Rest-LASr can serve as a reliable method for HCM patients who are unable to undergo exercise testing but require urgent evaluation of METS, which provides a basis for clinical treatment decision making and evaluation of treatment effect.